2016
DOI: 10.1007/978-3-319-27777-6_7
|View full text |Cite
|
Sign up to set email alerts
|

Parcellations and Connectivity Patterns in Human and Macaque Cerebral Cortex

Abstract: To decipher brain function, it is vital to know how the brain is wired. This entails elucidation of brain circuits at multiple scales, including microscopic, mesoscopic, and macroscopic levels. Here, we review recent progress in mapping the macroscopic brain circuits and functional organization of the cerebral cortex in primates-humans and macaque monkeys, in particular. There are many similarities across species in terms of overall patterns of cortical gray matter myelination as well as functional areas that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 57 publications
4
24
0
Order By: Relevance
“…connectional and functional studies, up to 180 distinct cortical areas have been identified in humans 32 (Glasser et al, 2016) and dozens in rodents (Kolb, 1990;Ng et al, 2009). Cortical areas are often 33 categorized as sensory, motor or associational, based on their connections with other brain areas.…”
Section: Introduction 30mentioning
confidence: 99%
See 1 more Smart Citation
“…connectional and functional studies, up to 180 distinct cortical areas have been identified in humans 32 (Glasser et al, 2016) and dozens in rodents (Kolb, 1990;Ng et al, 2009). Cortical areas are often 33 categorized as sensory, motor or associational, based on their connections with other brain areas.…”
Section: Introduction 30mentioning
confidence: 99%
“…Most sensory areas contain L4, and they are termed 35 'granular', whereas motor and associational areas usually do not have L4, and are hence 'agranular'. In 36 vertebrate evolution, cortex underwent disproportionally greater expansion in terms of the number of cells, 37 layers and functional areas compared to the rest of the brain, coinciding with the acquisition of increasingly 38 sophisticated cognitive functions (Jerison, 2009;Kaas, 2009; Man et al, 2013;Van Essen et al, 2016). 39…”
Section: Introduction 30mentioning
confidence: 99%
“…Line drawing summarizing the organization of projections between the amygdala and ventral stream visual cortical areas in adult macaques (reproduced from Freese & Amaral, 2005, pending approval) Do these connections show a similar pattern in human development? We know that macaque cortex is oriented differently than human cortex, and although homologies exist, the connectivity pattern in macaques may not necessarily perfectly map to humans (Passingham, 2009;Van Essen et al, 2016). Moreover, in humans, it is more challenging to study amygdalar connections, especially with respect to the basal vs. lateral nucleus and their connections to visual cortex.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of histological atlases for various NHP species provides an alternative means of guiding intracranial measurements and interventions. However, such atlases are inherently limited in their ability to account for differences in brain areal organization among animals, which can negatively impact experimentation when not properly considered (Cerliani et al, 2017; Gordon et al, 2017a, 2017b; Van Essen et al, 2016). …”
Section: Introductionmentioning
confidence: 99%